APPLICATIONS OF ARTIFICIAL INTELLIGENCE IN MEDICAL DIAGNOSIS (CIPEEX, 2025)
Artificial intelligence (AI) has established itself as a powerful tool in healthcare, especially incomputer-assisted medical diagnosis. This study aimed to analyze the contributions of AI inthe interpretation of medical images and its potential to improve diagnostic accuracy. Themethodology consisted of a literature review of articles indexed in the PubMed and Scopusdatabases, focusing on the use of machine learning algorithms in radiology, cardiology, andneurology. The results demonstrated that convolutional neural networks are capable ofdetecting early signs of diseases such as cancer, Alzheimer's, and cardiovascular conditions,often surpassing human accuracy in specific tasks. In addition, AI reduces diagnostic errorsand optimizes hospital management through the integration of electronic medical records.However, challenges remain, such as the need for diverse databases, algorithm transparency,and patient data protection. It is concluded that AI represents an innovative advance fordiagnostic medicine, but its safe and effective implementation requires professional trainingand strict regulations.
Keywords: Artificial Intelligence; Medical diagnosis; Medical imaging; Machine learning.